Analiza nivoa interleukina-17, interleukina-23, neopterina i nesfatina-1 u serumu Hašimoto pacijenata: Dijagnoza Hašimoto tireoiditisa - OZTURK, Ali (Journal of Medical Biochemistry, 2023)
Objective: Hashimoto’s thyroiditis (HT) is an autoimmune disorder affecting the thyroid gland and may present as goiter or atrophic thyroiditis that may result in various metabolic and inflammatory disorders. The aim of this study is to determine the changes in serum levels of interleukin-17 (IL-17), IL-23, neopterin, and nesfatin-1 parameters in HT patients and to evaluate the possible relationship among these parameters. Material and methods: 90 HT patients and 30 healthy individuals were included in this study. Demographic data of the patients included in the study were recorded and detailed physical examinations were performed. IL-17, IL-23, neopterin, and nesfatin-1 levels were measured in the serum samples of the participants by the ELISA method. Results: Serum IL-17, IL-23, neopterin, and nesfatin-1 levels were significantly higher in the HT group compared to the control group. Statistically significant differences were observed between all the groups except euthyroid HT versus HT treated with levothyroxine for nesfatin-1 at the 0.05 level. Conclusion: Our study showed that IL-17 and IL-23, neopterin, and nesfatin-1 levels are involved in the etiopathogenesis of HT especially the contribution of both IL-17 and IL-23 to the inflammation seen in autoimmune diseases such as Hashimoto’s. These variables could be used as potential biomarkers in the diagnosis, prognosis, and fellow up of HT disease. Further studies are needed to investigate the exact etiology of HT since its mechanism was not fully elucidated.